KARAKTERISTIK KEKERASAN SEKSUAL DI LINGKUNGAN PERGURUAN TINGGI - Makin, Oktaviani R. M. (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Sexual violence in higher education is a serious problem that can affect the academic community. This research aims to present an understanding of the characteristics of sexual violence in the tertiary environment by focusing on three main aspects;  types of sexual violence, risk factors and impacts.  The results of this research show that sexual violence in a college or campus environment involves various actions, including verbal harassment, physical harassment and non-physical harassment.  The main risk factors involve gender inequality, an surrounding culture that supports harmful behavior, and a lack of awareness about individual rights.  The impact involves physical, psychological and academic consequences for victims, as well as creating an unsafe and unhealthy campus environment.  Research also identifies challenges in reporting and addressing sexual violence on campus, including stigmatization of victims and lack of support from institutions.  Therefore, recommendations are submitted to improve response and support for victims in the campus environment.  It is hoped that this research can contribute to efforts to prevent and overcome sexual violence in higher education institutions